Comparative Analysis of Weekly Overburden Volume Using Total Station Survey and Truck Count Methods in Open-Pit Mine - Achmad Ainun Rafiqul; Helik Susilo; Muhammad Tri Aditya (West Science Interdisciplinary Studies, 2026)
Topographic surveying in mining operations is used to determine the actual progress volume of excavated material. In open-pit mining, overburden volume can be estimated from Total Station survey data through surface-to-surface volume calculation and compared with production volume obtained from Truck Count data. This study evaluates weekly overburden volume estimates derived from Total Station survey data and compares them with Truck Count volume data. The results showed that the volume difference in Week 1 was -43.11 BCM with a deviation of -1.1%. In Week 2, the difference was +126.06 BCM with a deviation of +1.6%. In Week 3, the difference was -59.87 BCM with a deviation of -1.6%, while in Week 4, the difference was -112.97 BCM with a deviation of -1.1%. The total volume difference was -89.89 BCM, with an overall deviation of -0.4%. The paired t-test indicated no statistically significant difference between Total Station survey-based volume estimates and Truck Count data. Therefore, both approaches can be considered comparable for estimating weekly overburden volume in open-pit mining operations.